2006
DOI: 10.1207/s15326942dn2902_3
|View full text |Cite
|
Sign up to set email alerts
|

Making Memories: A Cross-Sectional Investigation of Episodic Memory Encoding in Childhood Using fMRI

Abstract: In adults, the neural substrate associated with encoding memories connected to a specific time and place include the prefrontal cortex and medial temporal lobe (MTL). Using functional magnetic resonance imaging, this research studied the developmental trajectory of this frontal-MTL system by comparing 7- and 8-year-old children to those who were 10 or older in conditions that promoted episodic encoding. In 1 condition, participants generated verbs from nouns heard; in another, they listened to short stories fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
44
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 79 publications
10
44
2
Order By: Relevance
“…Declarative memory performance continues to develop throughout early and middle childhood and children become increasingly able to use strategies to efficiently encode, retain, and retrieve memories. Recent neuroimaging data confirms that while MTL activation predicts subsequent story recall in 7-8 year olds, activation in both MTL and prefrontal regions is associated with successful recall in 10-18 year olds (Chiu, Schmithorst, Douglas Brown, Holland, & Dunn, 2006). Chiu et al (2006) suggest that greater involvement of the prefrontal cortex in older children may be associated with age-related improvements in rehearsal and other encoding strategies during middle childhood.…”
Section: Discussionmentioning
confidence: 86%
“…Declarative memory performance continues to develop throughout early and middle childhood and children become increasingly able to use strategies to efficiently encode, retain, and retrieve memories. Recent neuroimaging data confirms that while MTL activation predicts subsequent story recall in 7-8 year olds, activation in both MTL and prefrontal regions is associated with successful recall in 10-18 year olds (Chiu, Schmithorst, Douglas Brown, Holland, & Dunn, 2006). Chiu et al (2006) suggest that greater involvement of the prefrontal cortex in older children may be associated with age-related improvements in rehearsal and other encoding strategies during middle childhood.…”
Section: Discussionmentioning
confidence: 86%
“…Mathematically, this is accomplished by performing a correlation on the residuals after regressing both reactivation and BC or AC performance on the controlling variable, XY performance. This analysis approach mirrors other studies that control for various factors such as age (22, 23) (23), general cognitive ability (20,24), or neural measures (25,26).] Specifically, we interrogated the relationships between (i) reactivation and BC memory performance and (ii) reactivation and AC inference performance, after statistically controlling for the effects of XY performance (our metric of general associative memory ability).…”
Section: Resultsmentioning
confidence: 99%
“…These include studies of both the automatic (memory processes that may not be under conscious control; e.g., feature sampling) and strategic (memory processes that are under conscious control; e.g., semantic clustering of to-be-remembered information) aspects of memory (both at encoding and retrieval) and studies of changes in children's knowledge base [56][57][58][59][60][61][62][63] . Results have shown that dlPFC regions that mediate the encoding of detailed episodic representations of experiences may have a protracted period of development than the MTL 52, 56-63 (but see [64][65][66] , so that memory formation early in childhood depends more on MTL contributions 26,36,38,[67][68] .…”
Section: Findings From Neurobiological Studiesmentioning
confidence: 99%